Fear of Missing Out and Student Interest in Stocks Investment during Covid-19 Pandemic - Dony Sudrajat (Journal of Economics Research and Social Sciences, 2022)
The emergence of the Covid-19 virus in Indonesia for the first time in March 2020 immediately had a significant impact on the condition of the domestic stock market. However, while the pandemic occurred, the number of capital market investors increased almost three times in 2019. Based on demographic data at the Indonesian Central Securities Depository, students are the second-highest number of investors. This study aims to analyze whether the fear of missing out factor affects student behavior in making stock investment decisions during the covid-19 pandemic. Fear of missing out on investment is the behavior of investors dependent on social media. Such behavior cannot be separated from students who tend to be more active in using social media, especially amid a pandemic. This study takes a case study of students from Universitas Muhammadiyah Yogyakarta, considering that this campus has a proactive student activity unit in terms of stock investment, namely the Capital Market Study Group. The data collection technique was in the form of a questionnaire distributed to 100 respondents, and the data was then processed using multiple regression analysis. This study shows that fear of missing out has a positive and significant relationship with student interest in stocks investment along with return variable, stock prices, and age.